Strategi Pengembangan UMKM Batik Tulis Goluak Loge Dalam Menunjang Ekonomi Kreatif di Desa Logas Kecamatan Singingi Kabupaten Kuantan Singingi - Safitri, Winda; Budiartiningsih, Rahmita; Indrawati, Toti; Zuryani, Hilmah (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine and analyze the internal and external conditions of the Goluak Loge hand-written batik MSME in Logas village to develop its business for the better. The data collection technique used in this study was a census with a sample size of 16 respondents consisting of 10 MSME workers and 6 constumers of the Goluak Loge hand-written batik MSME. The data used in this research are primary data and secondary data. The data analysis method used in this research is SWOT analysis. Based on the research results from the SWOT analysis, it show that the Goluak Loge hand-written batik MSME is in quadrant 1 (Agressive Strategy). From the results of the SWOT diagram drawing, it show that Goluak Loge hand-written batik MSME in Logas village has a strategy in developing its business both in the internal and external environment. This aggressive strategy focuses more on the SO (Strength-Opportunities) strategy, namely by optimizing strengths to take advantage of existing opportunities.